2022
DOI: 10.3390/ijerph19042064
|View full text |Cite
|
Sign up to set email alerts
|

Can Exposure to Environmental Pollutants Be Associated with Less Effective Chemotherapy in Cancer Patients?

Abstract: Since environmental pollutants are ubiquitous and many of them are resistant to degradation, we are exposed to many of them on a daily basis. Notably, these pollutants can have harmful effects on our health and be linked to the development of disease. Epidemiological evidence together with a better understanding of the mechanisms that link toxic substances with the development of diseases, suggest that exposure to some environmental pollutants can lead to an increased risk of developing cancer. Furthermore, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 93 publications
(104 reference statements)
0
14
0
Order By: Relevance
“…In a recent review by Lagunas-Rangel, the authors pose the question "Can Exposure to Environmental Pollutants Be Associated with Less Effective Chemotherapy in Cancer Patients?" The authors summarize evidence which strongly supports this hypothesis, which includes toxins which activate AhR (Lagunas-Rangel et al, 2022). Therachiyil examines this from the perspective of gynecological cancers.…”
Section: The Intersection Between Environmental Exposure and Cancer S...mentioning
confidence: 95%
“…In a recent review by Lagunas-Rangel, the authors pose the question "Can Exposure to Environmental Pollutants Be Associated with Less Effective Chemotherapy in Cancer Patients?" The authors summarize evidence which strongly supports this hypothesis, which includes toxins which activate AhR (Lagunas-Rangel et al, 2022). Therachiyil examines this from the perspective of gynecological cancers.…”
Section: The Intersection Between Environmental Exposure and Cancer S...mentioning
confidence: 95%
“…Several studies have shown that environmental pollutants affect cancer development and progression and these have been featured in various reviews (Boffetta, 2006 ; Brody et al., 2007 ; Koual et al., 2020 ; Lagunas‐Rangel et al., 2022 ; Wahlang, 2018 ). For example, some environmental pollutants can promote sustained growth by affecting the cell cycle or prevent apoptosis by avoiding activation of the intrinsic and/or extrinsic pathways.…”
Section: Mechanisms Linked To Carcinogenesis By Environmental Pollutantsmentioning
confidence: 99%
“…A growing body of epidemiological evidence as well as a better understanding of the mechanisms that link toxic substances to disease development suggests that exposure to some environmental pollutants may lead to an increased risk cancer development (Goodson et al., 2015 ; Koual et al., 2020 ). Several studies have raised the role of exposure to low doses of environmental pollutants in cancer initiation as well as cancer progression, suggesting that these compounds may promote cancer invasion and metastasis (Goodson et al., 2015 ; Koual et al., 2020 ; Lagunas‐Rangel et al., 2022 ; Ochieng et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, basal-like carcinomas, also known as triple-negative breast cancers (TNBC), are highly aggressive and metastasizing subtypes, with limited effective treatment strategies [ 105 , 106 ]. This scenario can be exacerbated by exposure to environmental pollution, which was reported to promote the metastasizing power and chemoresistance of different cancer cells [ 9 , 107 , 108 , 109 , 110 ]. In particular, smoking habits have been associated with an increased risk of mortality in breast cancer patients, probably due to a lower chemotherapy susceptibility and chemoresistance development [ 111 , 112 , 113 ].…”
Section: Strengths Limits and Future Perspectivesmentioning
confidence: 99%
“…Increasing epidemiological evidence has highlighted that the exposure to environmental pollution can increase the risk of various diseases, including cancer [ 1 , 2 , 3 , 4 , 5 , 6 ]; additionally, low-level pollutants have been shown to trigger cancer initiation and progression, and to promote tissue invasion, metastasis and chemoresistance [ 7 , 8 , 9 ]. Among the environmental toxicants, cigarette smoke (CS), both active and passive, is known to act as a promoting factor for the incidence of breast cancer, its aggressiveness, and recurrence [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%